Pelaksanaan Penimbangan Jual Beli Buah Kelapa Sawit Ditinjau Dari Fiqih Muamalah - Zulfan Efendi Hasibuan, Rabiul Awaliyah Daulay & (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
The background of the problem in this study is that the implementation of fruit weighing in the sale and purchase of oil palm in Dusun Cinta Damai, Pasir Tuntung Village is carried out using a hanging scale in the form of a round basket, and in its implementation it starts from the weighing that occurs between oil palm fruit sellers or farmers and buyers of oil palm fruit. or toke there is obscurity where the unclearness that is done is to reduce the scale by estimating the weight of the oil palm fruit bunches that do not consider the size of the oil palm fruit bunches or not by 15%. Palm oil to Ram on the same day Toke had to wait for the Ful Fruit Car Tub with oil palm fruit, The purpose of this study was to determine the Implementation of Fruit Weighing in Palm Oil Sales and Purchase and to Know the Overview of Muamalah Fiqh of Fruit Weighing Implementation In the Sale and Purchase of Palm Oil in Cinta Damai Hamlet, Pasir Tuntung Village, Kotapinang District, Labuhan Batu Selatan Regency. To reveal this problem in depth and thoroughly, researchers used a qualitative descriptive method. Then the Fiqih Muamalah Review of the Implementation of Fruit Weighing in the Sale and Purchase of Palm Oil in Cinta Damai Hamlet is not in accordance with the Rukun and terms of sale and purchase where the terms of sale and purchase in terms of the object must be seen in number, weight, measure and other measurements and there is no Gharar element (unclear) inside it. Meanwhile, the Buyer or Palm Fruit Toke estimates the weight of a Oil Palm Fruit bunch by 15%.